Radicalism in the Eyes of Linguistics: Bibliometric and Systematic Literature Review Methods - Retno Asihanti Setiorini; Untung Yuwono; Susi Yuliawati (Security Intelligence Terrorism Journal (SITJ), 2026)
This research was conducted to review global research developments related to articles on radicalism in linguistic analysis. Linguistics talks about language and language used by human to express their ideas/ideologies. For this reason, language could also be used to recognize ideas, including radical ideas or radicalism. Radical is an adjective that is often used to describe people or groups who have different thoughts or ideas from those people in general or the authority. Meanwhile, radicalism is a movement that seeks to change existing conditions (social, economic, political, etc.) in various ways, including violence. Apart from that, radicalisation attempts to spread and persuade others to embrace radicalism. This research uses bibliometric methods combined with a systematic literature review to find the research trends and gaps in the specific topic, radicalism in linguistics. Bibliometric analysis shows that the dominant topic talked about in radicalism in linguistics is radicalisation. The subject of radicalisation is widely discussed in extremism and terrorism. A radical language built a grouping dichotomy between us (in group) and them (out-group/ people outside in group). This grouping will give identity to a group and raise the difference between in-group and out-group. Radical groups would use the dichotomy to show victimhood, they would claim that the authority has been badly treating them so they are forced to counter by act violence. In communicating this, they use persuasive language, hate speech, insult, violent language, justification from selected scripture, and metaphor with distorted meaning.